2018
DOI: 10.1111/manc.12232
|View full text |Cite
|
Sign up to set email alerts
|

Together in bad times? Connectedness and spillovers in recession and boom

Abstract: Is connectedness across countries dependent on the state of the economy? We answer this question by applying the Diebold‐Yilmaz index in a non‐linear framework. Via a Threshold VAR model, we measure the connectedness of industrial production, inflation and financial variables for seven advanced economies. We find that global connectedness is sizable and business cycle dependent. Specifically, our results suggest that higher values are recorded during recessions. Financial and nominal connectedness display diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…2 Another novelty is the use of monthly data that, in terms of the standards of macroeconomic analysis, can be considered as high-frequency data. Although the use of such data is uncommon in related literature, Miescu (2019) is an exception to which this paper adds. The use of monthly data on CPI inflation and the unemployment rate is advantageous for a twofold reason.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…2 Another novelty is the use of monthly data that, in terms of the standards of macroeconomic analysis, can be considered as high-frequency data. Although the use of such data is uncommon in related literature, Miescu (2019) is an exception to which this paper adds. The use of monthly data on CPI inflation and the unemployment rate is advantageous for a twofold reason.…”
Section: Introductionmentioning
confidence: 92%
“…1 Along the same line, Antonakakis et al (2015) uncovered the existence of remarkable spillover effects between credit growth and output growth in the G7 economies. Miescu (2019), instead, proposed a nonlinear VAR approach to estimate the DY indices for industrial production, inflation, and stock price growth rates. The author confirmed and extended DY's (2015) results, and showed that European countries appear to be highly sensitive to fundamental shocks from the US and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another novelty is the use of monthly data that, in terms of the standards of macroeconomic analysis, can be considered as high-frequency data. Although the use of such data is uncommon in the related literature, Miescu (2019) is an exception to which this paper adds. The use of monthly data on CPI inflation and the unemployment rate is advantageous for a twofold reason.…”
Section: Introductionmentioning
confidence: 93%
“…1 Along the same line, Antonakakis et al (2015) uncovered the existence of remarkable spillover effects between credit growth and output growth in the G7 economies. Miescu (2019), instead, proposed a nonlinear VAR approach to estimate the DY indices for industrial production, inflation, and stock price growth rates. The author confirmed and extended DY's (2015) results, and showed that European countries appear to be highly sensitive to fundamental shocks from the USA and Japan.…”
Section: Introductionmentioning
confidence: 99%